Co‐occurrence of progressive hemifacial atrophy due to morphea with homolateral segmental vitiligo: A case report - Pukar Chapagain; Sudha Agrawal (Clinical Case Reports, 2021)
Abstract Simultaneous occurrence of progressive hemifacial atrophy due to morphea and homolateral segmental vitiligo, younger onset, rapid progression followed by stabilization and dermatomal distribution suggests a possible relationship between them.